2017
DOI: 10.1186/s12864-016-3457-9
|View full text |Cite|
|
Sign up to set email alerts
|

A comparative genomic analysis of putative pathogenicity genes in the host-specific sibling species Colletotrichum graminicola and Colletotrichum sublineola

Abstract: Background Colletotrichum graminicola and C. sublineola cause anthracnose leaf and stalk diseases of maize and sorghum, respectively. In spite of their close evolutionary relationship, the two species are completely host-specific. Host specificity is often attributed to pathogen virulence factors, including specialized secondary metabolites (SSM), and small-secreted protein (SSP) effectors. Genes relevant to these categories were manually annotated in two co-occurring, contemporaneous strains of C. graminicola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 142 publications
4
41
0
Order By: Relevance
“…However, the drop in orthology was less dramatic, emphasizing the contribution of non-coding regions in generating diversity within the genus. The extent of synteny between C. tanaceti and C. higginsianum was high and very similar to the percentage synteny previously reported for the two graminicola complex species, C. sublineola and C. graminicola [150]. This suggested that even though there was high diversity within the genus, the species in the same species complex tend to share more synteny than the between species complexes.…”
Section: Evolution Of Pathogenicity Genessupporting
confidence: 86%
“…However, the drop in orthology was less dramatic, emphasizing the contribution of non-coding regions in generating diversity within the genus. The extent of synteny between C. tanaceti and C. higginsianum was high and very similar to the percentage synteny previously reported for the two graminicola complex species, C. sublineola and C. graminicola [150]. This suggested that even though there was high diversity within the genus, the species in the same species complex tend to share more synteny than the between species complexes.…”
Section: Evolution Of Pathogenicity Genessupporting
confidence: 86%
“…Several draft and optical map-based genomes of species in the genus Colletotrichum have been published in past years, addressing and comparing the molecular mechanisms governing the pathogenic life of the species (O'Connell et al, 2012;Baroncelli et al, 2014;Crouch et al, 2014;Gan et al, 2016;Zampounis et al, 2016;Buiate et al, 2017). Although an increasingly more comprehensive understanding of the pathogenesis of these pathogens is thus emerging, the key genes determining compatibility and virulence in the host have not been identified, with the exception of the C. lindemuthianum-Phaseolus vulgaris pathosystem, which follows a gene-for-gene concept as described by Flor in 1946(Luna-Mart ınez et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPRFinder was used to identify the CRISPR ( Grissa et al, 2007 ). Predicted genes were compared with the Pathogen-Host Interaction (PHI) database ( Urban et al, 2015 ) using the BLASTp method and an e -value cutoff of 1.0 × 10 −5 ( Buiate et al, 2017 ). The annotation results were verified using the Artemis ( Rutherford et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%